EU in the Power Equation of Global Containerized Maritime Trade - Bosneagu, Romeo; Coca, Carmen Elena; Sargu, Lilia; Daneci-Patrau, Daniel; Corduneanu, Dumitru (Acta Universitatis Danubius. Œconomica, 2022)
Container shipping can be described as the world's first truly global industry. Europe is at the forefront of global containerized seaborne trade. It is also relevant that this industry, more than any other, makes it possible for a worldwide economy to function. It connects countries, markets, businesses and people, enabling them to buy and sell goods at a level not previously possible. As the consuming party, the population has become accustomed to having goods from all parts of the world, which it can now easily access. The current reality is that the needs of a rapidly growing population can only be met by transporting goods and resources between countries. The container shipping industry has streamlined this process and changed the face of the global economy, which benefits consumers by creating choice, boosting economies and creating new jobs. Costs for consumers are reduced, efficiency is improved, and this minimizes environmental impact.